2014
DOI: 10.1080/09640568.2014.984017
|View full text |Cite
|
Sign up to set email alerts
|

More than money: how multiple factors influence householder participation in at-source stormwater management

Abstract: RossRakesh (2014): More than money: how multiple factors influence householder participation in at-source stormwater management, Journal of Environmental Planning and Management, Urban stormwater run-off is a threat to stream ecosystems. New approaches to stormwater management aim to protect urban streams from such impacts, by retaining, treating and using stormwater at its source. As up to »50% of runoff from urban surfaces comes from private property, fostering stormwater retention requires effective househo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(47 citation statements)
references
References 54 publications
0
46
1
Order By: Relevance
“…For example, current approaches to catchment-scale stormwater management, such as rain gardens, infiltration systems, permeable pavements, green roofs, and stormwater harvesting systems require public support and participation, which can be difficult to obtain (Roy et al 2008, Brown et al 2016. Furthermore, there are several other characteristics of riparian restoration that make it a beneficial restoration option.…”
Section: Management Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, current approaches to catchment-scale stormwater management, such as rain gardens, infiltration systems, permeable pavements, green roofs, and stormwater harvesting systems require public support and participation, which can be difficult to obtain (Roy et al 2008, Brown et al 2016. Furthermore, there are several other characteristics of riparian restoration that make it a beneficial restoration option.…”
Section: Management Implicationsmentioning
confidence: 99%
“…First, local-scale riparian restoration tends to be less costly and logistically simpler than managing stormwater runoff at the catchment scale. For example, current approaches to catchment-scale stormwater management, such as rain gardens, infiltration systems, permeable pavements, green roofs, and stormwater harvesting systems require public support and participation, which can be difficult to obtain (Roy et al 2008, Brown et al 2016). Brown et al (2016) reported 39.5% participation by eligible households in a catchment-scale residential water harvesting program in Melbourne, Australia, which is unlikely to substantially reduce the hydrologic effects of urbanization (Vietz et al 2014).…”
Section: Management Implicationsmentioning
confidence: 99%
“…Using vegetable raingardens as an extension of traditional home vegetable gardening would help to overcome the common negative perception that raingardens offer no tangible benefit to people (Brown et al, 2014). Vegetable raingardens could have the particular benefit of overcoming constraints on vegetable gardening related to water scarcity.…”
Section: Introductionmentioning
confidence: 99%
“…167 Although such experiments are ambitious and challenging, 169 they are a rigorous field test for how well LID technologies insulate streams from catchment urbanization. The project has already generated important lessons in relation to community engagement, 37,170 institutional aspects, 171 and the performance of LID technologies in flood reduction. 172 There are some early signs that the retrofit may be improving water quality in the creek.…”
Section: 67mentioning
confidence: 99%
“…Acquiring and maintaining public support for LID technologies requires demonstrating that they are effective at minimizing flood risk and the negative impacts of urbanization on human and ecosystem health. 1,37,38 In this review, we explore: (1) the variety of modeling approaches available for supporting LID selection and evaluation; (2) technologies available for stormwater infiltration and harvesting; and (3) implementation challenges including maintenance, climate change, path dependence, and site-specific constraints. A number of review articles have been written on LID technologies and their use for mitigating hydrologic, water quality, and ecological symptoms of the urban stream syndrome.…”
Section: Introductionmentioning
confidence: 99%